NUTRITIVE APPROACHES TO THE CORRECTION AND PROPHYLAXIS OF MICROELEMENTAL STATUS DISORDERS IN CHILDREN - A.A. Ploskireva (Вопросы современной педиатрии, 2011)
The article presents the literature review of one of the significant problems in modern threpsology — microelemental insufficiency. Main micronutrients, their significance and sources are described. Author pays attention to the opportunities of nutritive approaches to the correction and prophylaxis of microelemental status disorders in children with modern enriched milk products.Key words: children, microelements, insufficiency, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (2): 141–145)